The risks and benefits of Open Migration Policy in Asia-Pacific region - Madiyem Layapan; Romzi Ationg; Anantha Raman Govindasamy; Mohd. Azri Ibrahim; Mohd. Sohaimi Esa; Sirahim Abdullah; Abang Mohd Razif Abang Muiz (Pennwell Corporation, 2020)
The advent of post-colonial era shows Asia-Pacific regions such as Malaysia, China, Korea, Australia, New Zealand, and Japan have restricted migration policy. Despite the restriction, intellectual debates about the prospect of having open migration grew. The debates generally concentrate on what exactly are the benefits and risks of introducing open migration. This paper seeks to discuss what exactly are the benefits and risk of having open migration policies. To do so, it is argued that explanation on what exactly are the benefits and risk of having open migration policy must be tracked down by analyzing the security, economic and cultural issues in receiving country. Accordingly, based on literature as well as documents review, this paper suggest that open migration policy can be a source of security threats in receiving country which including the way that open migration may bring about uncontrolled population growth. In contrast, open migration policy may bring about economic and cultural enrichment in receiving country. Therefore, given the fact that open migration may bring about risks and benefits to receiving countries, this paper also explores the prospect of migration policy improvement as means of application for not only preventing the country form any risks, but also consolidating the economic and cultural enrichment though migration policy.